DEVELOPING PANCOH ECOTOURISM-ORIENTED THEMATIC STRIP COMICS FOR ELEMENTARY SCHOOL STUDENTS - Rezkita, Shanta; Mukaromah, Latifatun (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Education in the era of disruption must maintain the value of the nation's character. Ecotourism Pancoh has the potential as an educational space for environmental character. The packaging in comics is useful for civilizing literacy. This study aimed to describe the way of developing and knowing the quality and feasibility of ecotourism-oriented thematic strip comics. This study was research and development by adapting the model of Borg & Gall. The data were collected by observation, unstructured interviews, and questionnaires. The comic trials were conducted for fifth grade students of Bhayangkara Elementary School, Yogyakarta. The data were analyzed by using qualitative and quantitative techniques. The assessment score of the media expert validation was 92,11 (very good), material expert was 95,33 (very good), teacher was 95,50 (very good), and student responses were 100 (very good). Thus the Pancoh ecotourism-oriented thematic strip comic was very feasible as a learning resource for elementary school students.